Stewardship : Living a Biblical Call - Evans, Bernard F., 1943- (Book collections on Project MUSE., 2014)
In Stewardship: Living a Biblical Call, Bernard Evans presents an accessible and easily understood biblical and theological foundation for giving that both parishioners and stewardship leaders will find practical and valuable. In focused chapters, the many aspects of stewardship are named and described, assisting readers in recognizing gifts and actions that make practicing stewardship far more than a financial proposition. Grounded in years of practical work in this area with parish leaders, Evans adeptly ties the Catholic invitation to stewardship to biblical foundations as well as the social teaching of the church. A clear, concise, readable work, Stewardship: Living a Biblical Call also engages key questions of the age, such as ecological stewardship and care for body, mind, and spirit. Evans explores the communal and personal actions that help every believer proclaim the reign of God.